Analysis of Financial Support to the Surviving Spouses and Children of Casualties in the Iraq and Afghanistan Wars - Miller, Amalia R. (RAND Corporation, 2012)
Examines how the death of service members affects the subsequent labor market earnings of surviving spouses and the extent to which survivor benefits provided by the Department of Defense, the Department of Veterans Affairs, and the Social Security Administration compensate for lost household earnings. Also assesses the extent to which payments surviving spouses and children receive compensate for earnings losses attributable to combat death.